Formation And Durability Investigation On Graphene-Based Superhydrophobic Coating - Karim, Mohamad Afiffudin (Universiti Sains Malaysia, 2018)
Hydrophobic coatings are widely used in automotive, electronic, medical, paint coating, textiles and many other industries. In order to expand the potential application, transition from hydrophobic to super-hydrophobic which exhibit water contact angle (WCA) from 90' to more than 150º must be considered by its requirement. The main focus of this work is to improve hydrophobicity by incorporate nanoparticle into silane to satisfy both hydrophobic surface requirements which are rough surface and low surface energy. In this work, Graphene, Graphene Oxide and modified graphene Oxide nanoparticle was incorporate in Polydimethylsiloxane (PDMS) which used as the hydrophobic precursor due to its properties of non-fluorinated and low surface energy material. The nanoparticles were deposited on glass substrate by spraying method. The differences of nanoparticles in roughness from AFM analysis and molecular surface chemistry from FTIR analysis have influenced the wettability behaviour; whereby high roughness resulted in high water contact angle (WCA) and Sliding angle (SA). G-PDMS and mGO-PDMS has WCA of 159' and 162', while the SA is 30' and 25', respectively. GO-PDMS has lower WCA of 14' and SA is 90'. Durability of the film were eveluvated via peel off test, UV aging and acid-base stability at pH 4 and pH 10. Peel of test shows, G-PDMS has better stability compare to PDMS-GO and PDMS-mGO. All the 3 films has better durability in basic environment than acidic environment. G-PDMS and mGO-PDMS has better UV aging durability than GO-PDMS.